PENGARUH MODAL INTELEKTUAL (INTELLECTUAL CAPITAL), PROFITABILITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN - Permatasari, Difa; ., Sutapa (Jurnal Ilmiah Penelitian Mahasiswa, 2025)
The purpose of this research is to examine how Intellectual Capital, Profitability, and Institutional Ownership affect firm value. The investment potential for future business expansion is reflected in the firm of the company, which is maximized by the share price to benefit the owner. The research population is manufacturing companies listed on the IDX between 2020 and 2023. Sampling using purposive sampling technique was the sampling strategy used in this research, and 64 companies were obtained. The company's Annual Report provides secondary data used in this research. Multiple linear regression analysis techniques were used in this research to test the hypothesis. The findings of this study show that VACA, VAHU, Profitability have a significant and positive impact on firm value. Meanwhile, firm value is significantly negatively influenced by STVA and institutional ownership.Keywords: VACA, VAHU, STVA, Profitability, Institutional Ownership, Firm Value